Surgical complications of round worm infestation - Vagholkar, Ketan; Pawanarkar, Amish; Vagholkar, Suvarna; Jawanjal, Avinash; Subudhi, Subashchandra; Chauhan, Parthsarthi; Agrawal, Purva (International Journal of Research in Medical Sciences, 2017)
Round worm infestation is common in the tropical countries. Ascaris lumbricoides can cause a variety of complications in the abdomen ranging from colic to perforative peritonitis. As majority of abdominal complications require surgical intervention awareness of the complications is pivotal to the attending surgeon. The surgical complications of roundworm infestation are discussed in this article.